Pyruvate Dehydrogenase Contributes to Drug Resistance of Lung Cancer Cells Through Epithelial Mesenchymal Transition - Cevatemre, Buse; Ulukaya, Engin; Dere, Egemen; Dilege, Sukru; Acilan, Ceyda (Frontiers in Cell and Developmental Biology, 2022)
Recently, there has been a growing interest on the role of mitochondria in metastatic cancer research. There are several reports showing that highly metastatic cancer cells preferentially use glycolysis over mitochondrial respiration for energy production. Pyruvate dehydrogenase enzyme complex (PDH) has been shown to be responsible for this switch in some cancers. Since epithelial mesenchymal transition (EMT) is proposed to be one of the key driving forces of metastasis, the molecular connections between cancer cell metabolism and EMT may reveal underlying mechanisms and improve our understanding on metastasis. In order to explore a potential role for PDH inhibition on EMT and associated drug resistance, we took both pharmacological and genetic approaches, and selectively inhibited or knocked down PDHA1 by using Cpi613 and shPDHA1, respectively. We found that both approaches induced morphological changes and characteristics of EMT (increase in mesenchymal markers). This change was accompanied by a more rapid wound healing and an increased migration potential. Interestingly, cells were more resistant to many of the clinically used chemotherapeutics following PDHA1 inhibition. Furthermore, the TGFβRI (known as a major inducer of the EMT) inhibitor (SB-431542) together with the PDHi, was effective in reversing EMT. In conclusion, interfering with PDHA1 activity induced the EMT phenotype, and more importantly resulted in resistance to chemotherapeutic drugs. Therefore, our study demonstrates the need for careful consideration of PDH-targeting approaches in cancer treatment.